Evaluation of extracts from the apple mangrove (Sonneratia caseolaris Engler) as feed additive for shrimp, Penaeus monodon postlarvae - Avenido, Pedro Musong (Miagao, Iloilo University of the Philippines Visayas, 2013)
The study aimed to evaluate extracts of the apple mangrove (Sonneratiacaseolaris) as agent of prophylactic/therapeutant and immunostimulant for the culture of Penaeusmonodon. General typesofcompounds that might be present in the leaf and twig extracts were glycosides, triterpenes, sterols and flavonoids as determined by Thin Layer Chromatography (TLC). Glycosides were present in all organic solvent extracts. Based on the mean clear zone of inhibition, twig extract exhibited higher antibacterial activity than did the leaf extract. Furthermore, the methanolic extract of the twig gave the highest antibacterial activity and was diet (commercially available shrimp starter feed) and was tested at three feeding frequencies (2, 3 and 4 times daily) for its effect on growth, feed conversion ratio and survival against a control treatment (pure basal diet) fed three times daily. Final average body weight (ABW) and length, specific growth rate (SGR) and feed conversion ratio (FCR) of shrimps fed the medicated diets were all comparable to those fed the control diet with the exception of those fed the medicated diet twice daily which exhibited poorest in all three parameters. Survival of shrimps fed medicated diets was all superior to those fed the control diet. Activities of amylase, total protease and lipase, trypsin-like and chymotrypsin-like enzymes were measured following a 60d-1 feeding of the control and medicated diets at three feedingfrequencies. Amylase and total protease activities were higher in shrimps fed medicated diet, only when it was fed four times daily. Lipase, trypsin- and chymotrypsin-like activities were higher in all medicated diets regardless of feeding frequency. Indices of Immune response were measured, namely respiratory burst, phagocytic, phenoloxidase (PO) and bacterial growth inhibitory activities, following feeding shrimps the control and medicated diets for 60d-1. There were no significant differences in respiratory burst activities between treatments due to high variability but shrimps fed medicated diets at higher feeding frequencies (3 and 4 times daily) exhibited considerably higher values than did the other two groups of shrimps. Phagocytic and PO activities were significantly higher in shrimps fed medicated diets at all feeding frequencies than did those fed the control diet ; activities were not significantly different between those fed medicated diets. Bacterial survival index was significantly higher in shrimps fed the control diet than did those fed medicated diets ; indices of shrimps fed medicated diets were not significantly different. In summary, methanolic extracts of S. caseolaris twigs did not affect growth rate and feed conversion efficiency but increased survival. It promoted digestion of major nutrients by increasing the activities of amylase, total protease, lipase, trypsin-like and chymotrypsin-like enzymes at various feeding frequencies. It did not affect respiratory burst activity, but enhanced the immune resistance of shrimp by promoting bith phagocytic and PO activities and lowering bacterial survival. In conclusion, the apple mangrove extract could be employed in shrimp culture as a prophylactic therapeutant as well as an immunostimulant
Dissertation (Doctor of Philosophy in Fisheries-Aquaculture) -- Miagao, Iloilo : University of the Philippines Visayas, April 2013.
Keywords: Apple mangrove